2007
DOI: 10.2527/jas.2006-288
|View full text |Cite
|
Sign up to set email alerts
|

Influence of endosperm vitreousness and kernel moisture at harvest on site and extent of digestion of high-moisture corn by feedlot steers

Abstract: Six ruminally and duodenally cannulated Angus-Jersey crossbred steers (450 kg of BW) were used in a 6 x 6 Latin square to evaluate the effect of kernel vitreousness and moisture on intake and digestibility of high-moisture corn. Arranged in a 2 x 3 factorial, diets included a floury (FLO) or a vitreous (VIT) endosperm corn hybrid harvested at 28.1% (DRY), 31.2% (MID), or 35.7% (WET) kernel moisture content. Diet DM consisted of 88.25% high-moisture corn, 6% chopped alfalfa hay, 2% corn gluten meal, 0.75% urea,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 20 publications
2
16
1
1
Order By: Relevance
“…They found that flaking hybrids eliminated differences between harder and softer hybrids observed within DRC. Utilizing only HMC, Szasz et al (2007) found that more vitreous hybrids were more digestible than less vitreous hybrids, due mostly to an increase in postruminal starch digestibility, which is in disagreement with previous research utilizing DRC (Corona et al, 2006).…”
Section: Introductioncontrasting
confidence: 96%
“…They found that flaking hybrids eliminated differences between harder and softer hybrids observed within DRC. Utilizing only HMC, Szasz et al (2007) found that more vitreous hybrids were more digestible than less vitreous hybrids, due mostly to an increase in postruminal starch digestibility, which is in disagreement with previous research utilizing DRC (Corona et al, 2006).…”
Section: Introductioncontrasting
confidence: 96%
“…Differences of DM concentration in HMC (74.0%) and corn grain in WCS (56.6%) could also have had a significant impact on organic matter and starch digestibility, and therefore on the energy supply for milk production. In feedlot steers, Szasz et al (2007) reported a linear increase in effective degradability of DM and starch with decreasing levels in DM concentration from 72% to 64% in HMC using the in sacco technique. However, total tract digestibility of starch was not different between treatments (Szasz et al, 2007).…”
Section: Cs and Diet Compositionsmentioning
confidence: 98%
“…In feedlot steers, Szasz et al (2007) reported a linear increase in effective degradability of DM and starch with decreasing levels in DM concentration from 72% to 64% in HMC using the in sacco technique. However, total tract digestibility of starch was not different between treatments (Szasz et al, 2007). This may explain why the 4% fat-corrected milk (FCM) and efficiency of milk production was not different between WCS and RCS in the current experiment (Table 5).…”
Section: Cs and Diet Compositionsmentioning
confidence: 98%
“…These results show that for the protein matrix, a component which complicates the ruminal starch digestion, hybrids with dent endosperm must be chosen to make silage because they have a lower vitreous proportion in the grain. Vitreousness is highlighted as an important parameter to be considered from the inferences of Szasz et al (2007), who claimed that corn hybrids differ minimally in starch content in the grains while there are large differences in vitreousness. Corona et al (2006) and Cantarelli et al (2007) verified the higher digestibility coefficient of grain dry matter in dent genotypes compared with flint grains in corn hybrids.…”
Section: Resultsmentioning
confidence: 99%